2016
DOI: 10.1108/jpbm-01-2015-0786
|View full text |Cite
|
Sign up to set email alerts
|

Exploring antecedents and consequences of young consumers’ perceived global brand equity

Abstract: Purpose With the expansion of globalization, the increased competitive environment has led to the diffusion of brands across borders and cultures. Furthermore, young consumers represent an optimal segment for the proliferation of global consumer culture (GCC). This paper aims to examine the relationship between acculturation to global consumer culture (AGCC), perceived brand equity, attitudes toward the brand and brand resonance in the global sportswear brands context among young consumers in the USA. Design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
(71 reference statements)
2
21
0
1
Order By: Relevance
“…The brand support team from the company side seems to not be able to cope with the speed of change. Markets have become more global, brands have become diffused across borders and cultures (Frank and Watchravesringkan, 2016) and the technological advances have enhanced the cultural borrowing and the interaction of interested parties across the globe. The wide use of the internet and social networks such as Facebook, Twitter, Instagram and Pinterest facilitates the process of consumers finding likeminded individuals that support the brands they like without any constrain of geographic boundaries (Dessart et al, 2015;Simon et al, 2016;Tafesse, 2016).…”
Section: Other Things Have Changedmentioning
confidence: 99%
“…The brand support team from the company side seems to not be able to cope with the speed of change. Markets have become more global, brands have become diffused across borders and cultures (Frank and Watchravesringkan, 2016) and the technological advances have enhanced the cultural borrowing and the interaction of interested parties across the globe. The wide use of the internet and social networks such as Facebook, Twitter, Instagram and Pinterest facilitates the process of consumers finding likeminded individuals that support the brands they like without any constrain of geographic boundaries (Dessart et al, 2015;Simon et al, 2016;Tafesse, 2016).…”
Section: Other Things Have Changedmentioning
confidence: 99%
“…Batra et al (2000) have identified a strong relationship between brand image and brand attitude in India for local, nonlocal and even for blended or hybrid brands. Frank and Watchravesringkan (2016) have also identified a close relationship between brand image and brand attitude among global brands. However, from Keller's (1993) point of view, if brand attitude is a part of brand image, brand attitude should be a driver of brand image (Kirmani and Zeithaml, 1993).…”
Section: Hypothesis Developmentmentioning
confidence: 93%
“…As customer emotions move from negative to positive, customer loyalty is expected to ascend. Recent empirical study (Frank, 2016) also revealed a positive relationship between perceived brand equity and brand resonance. Hence, pre-purchase perceived brand equity would further develop brand loyalty on the basis of post-purchase experience.…”
Section: Post Purchase Behavior Of Consumers and Its Further Relationmentioning
confidence: 94%